Physical association of starch biosynthetic enzymes with starch granules of maize endosperm. Granule-associated forms of starch synthase I and starch branching enzyme II. - Mu-Forster, C (1996)
Antibodies were used to probe the degree of association of starch biosynthetic enzymes with starch granules isolated from maize (Zea mays) endosperm. Graded washings of the starch granule, followed by release of polypeptides by gelatinization in 2% sodium dodecyl sulfate, enables distinction between strongly and loosely adherent proteins. Mild aqueous washing of granules resulted in near-complete solubilization of ADP-glucose pyrophosphorylase, indicating that little, if any, ADP-glucose pyrophosphorylase is granule associated. In contrast, all of the waxy protein plus significant levels of starch synthase I and starch branching enzyme II (BEII) remained granule associated. Stringent washings using protease and detergent demonstrated that the waxy protein, more than 85% total endosperm starch synthase I protein, and more than 45% of BEII protein were strongly associated with starch granules. Rates of polypeptide accumulation within starch granules remained constant during endosperm development. Soluble and granule-derived forms of BEII yielded identical peptide maps and overlapping tryptic fragments closely aligned with deduced amino acid sequences from BEII cDNA clones. These observations provide direct evidence that BEII exits as both soluble and granule-associated entities. We conclude that each of the known starch biosynthetic enzymes in maize endosperm exhibits a differential propensity to associate with, or to become irreversibly entrapped within, the starch granule.